Development of analytic rubric for assessing written assignments for evaluating higher order cognition in the first phase neuroanatomy module - Anita Rani; Sarika Gupta; Garima Sehgal; Rameshwari Singhal (Wolters Kluwer Medknow Publications, 2023)
Background: Competency-based medical education has been recently launched for MBBS students in India by the National Medical Council. Successful implementation of the new curriculum requires not only concrete evidence of acquisition of competencies but also proper feedback to students for his growth in the required direction. In the first phase MBBS program, in the neuroanatomy module, frequently students' ability to correlate patients' signs and symptoms is asked during examinations to assess higher order cognitive skill. These questions are usually asked in written assessments as short essay responses. Currently, the use of analytic rubrics is limited in medical students' written assessment. Teachers use their self-developed criteria to grade students for such answers. Analytic rubrics have evidence to improve case writing, presentation, surgical and soft skills. The present study aims to develop an analytic rubric to assess critical thinking abilities in written exams. Methodology: The study was carried out at KGMU, Lucknow. After developing the criteria and grading statements, two rounds of modified Delphi method of consensus building were conducted by involving 20 subject experts. The item-level validity index of 0.7 or above was set to retain the descriptors. Results: After the two rounds of consensus, an analytic rubric with 7 criteria, each with 3 performance levels as excellent (>75%), satisfactory (50%-75%), and unsatisfactory (<50%), was developed. All criteria and level descriptors were having content validity index above 0.7. Conclusion: The developed analytic rubrics with clear expectations will help learners to set their learning goals and faculty to assess their level of achievements more objectively.